“Las reglas IBA para la prueba en el arbitraje y las reglas sobre la testimonial en el proceso civil peruano" - Avendaño Valdez, Juan Luis (2017)
This work addresses the problem of why witness testimony is not valued as evidence on civil procedures. This situation is different from what occurs in court procedures on criminal and labour law matters, or even in arbitration procedures. Research aims to discover the reasons for this difference, by comparing the rules of evidence of the Peruvian civil procedure with those of the International Bar Association - IBA. The comparison proved to be useful as it finds the causes on the breach of the principle of truth and on the lack of technical knowledge for the use of testimony as a valuable means of evidence. The author highlights the advantages of certain features contained in the rules of evidence of the IBA, which he proposes to incorporate into the Peruvian civil procedure. Accordingly, the author suggests that the Peruvian civil procedure could incorporate features such as witness written statement and cross-examination, as well as other types of interrogatories which all together could help overcoming the problems found in Peru which limit the use of witness testimonials.